Food at your doorstep? examining customer loyalty towards online food delivery applications - Liu, Xin; Lim, Xin Jean; Cheah, Jun Hwa; Ng, Siew Imm; Kamal Basha, Norazlyn (Emerald Publishing, 2023)
Purpose: This study empirically investigated the different attributes (i.e. convenience, online reviews, online ratings, visual appeal and various food choices) of food delivery applications (FDAs) that impacted customers' perceived benefits, satisfaction and loyalty. Price consciousness was positioned as the moderator while customer satisfaction was positioned as the mediator. Design/methodology/approach: Utilizing the purposive sampling technique, 360 useable respondents were gathered from existing FDAs' customers in China. Partial least squares structural equation modelling (PLS-SEM) was employed to verify the interrelationships among variables. Findings: The results confirmed the significant impact of four FDA attributes (i.e. convenience, online ratings, visual appeal and various food choices) on perceived benefits. Customer satisfaction positively influenced loyalty. Moreover, the mediating role of customer satisfaction and the moderating role of price consciousness were confirmed. Practical implications: FDA operators should engage in providing more benefits to stimulate satisfaction and loyalty among customers. Promotion discounts remain a key factor in enhancing the satisfaction and loyalty of price-conscious customers. Originality/value: This study extends the applicability of the stimulus–organism–response (SOR) framework and enriches FDA literature by assessing the external stimuli, organisms and moderating factors that trigger customer loyalty.